The impact of safety culture dimensions on workplace accidents: an application in the Moroccan automotive industry (International Journal of Occupational Safety and Health, 2024)
Introduction: There is a general accord that safety culture is multidimensional. but limited research and publications are there about those dimensions. Almost one-third of the publications presenting safety culture definitions do not discuss the safety culture dimension nor the relationship between the safety culture dimensions and workplace accidents.  To further understand the factors influencing this correlation. it appeared appropriate in this situation to investigate the relationship between the safety culture dimensions and occupational accidents. This study aims to identify the safety culture dimensions in the automotive industry in Morocco and its relations with occupational accidents.  Methods: A study was done with 35 of the largest automotive companies in Morocco. the effects of Safety Culture dimensions on workplace accidents in the automotive industry were examined based on the literature review. and a measurement questionnaire that was created with a sample of numerous automotive workers for 2 months in the winter semester of November and December 2022.Results: The results highlight that the safety culture dimensions have a strong influence on avoiding accidents especially the safety culture's dimensions which present 40%. In addition, the COVID-19 period had a big impact on the number of occupational accidents in the automotive sector. 40.54% of these occupational accidents occurred between 2020 and 2022.Conclusion: Based on the results gained from the Questionnaire the common safety culture dimensions are employees’ attitudes or unsafe behaviors, lack of staff participation, and inadequate supervision.